Congenital Trypanosoma cruzi Transmission in Santa Cruz, Bolivia - Bern, Caryn (Clin Infect Dis, 2009)
BACKGROUND: We conducted a study of congenital Trypanosoma cruzi infection in Santa Cruz, Bolivia. Our objective was to apply new tools to identify weak points in current screening algorithms, and find ways to improve them. METHODS: Women presenting for delivery were screened by rapid and conventional serological tests. For infants of infected mothers, blood specimens obtained on days 0, 7, 21, 30, 90, 180, and 270 were concentrated and examined microscopically; serological tests were performed for the day 90, 180, and 270 specimens. Maternal and infant specimens, including umbilical tissue, were tested by polymerase chain reaction (PCR) targeting the kinetoplast minicircle and by quantitative PCR. RESULTS: Of 530 women, 154 (29%) were seropositive. Ten infants had congenital T. cruzi infection. Only 4 infants had positive results of microscopy evaluation in the first month, and none had positive cord blood microscopy results. PCR results were positive for 6 (67%) of 9 cord blood and 7 (87.5%) of 8 umbilical tissue specimens. PCR-positive women were more likely to transmit T. cruzi than were seropositive women with negative PCR results (P < .05). Parasite loads determined by quantitative PCR were higher for mothers of infected infants than for seropositive mothers of uninfected infants (P < .01). Despite intensive efforts, only 58% of at-risk infants had a month 9 specimen collected. CONCLUSIONS: On the basis of the low sensitivity of microscopy in cord blood and high rate of loss to follow-up, we estimate that current screening programs miss one-half of all infected infants. Molecular techniques may improve early detection.